PENGARUH PEMBIASAAN PENGGUNAAN BAHASA JAWA DALAM PEMBENTUKAN KARAKTER PATRIOTISME SISWA SEKOLAH DASAR - Pamungkas, Tri Aji; Rigianti, Henry Aditia (LPPM Institut Pendidikan Nusantara Global, 2023)
Many children don't know the difference between conversations with their parents and their peers in this era. In Javanese society, we already see fewer and fewer children who don't experience difficulties in behaving around their parents, some don't even have it at all. Children are increasingly far from noble values ​​and local wisdom. The methodology for writing this article is a literature review of research results published in national publications. Procurement of habituation to the use of the Javanese language for communication in elementary schools can be one of the means to be able to preserve Javanese culture and language. Besides that, it can also increase the value of the character of love for the motherland and also children's patriotism. The provision of habituation to the use of the Javanese language in elementary schools can be associated with or can influence the love of the motherland and patriotism of elementary school students.